Hiwar Method In Increasing The Speaking Skill Of Ma'had Al-Jami'ah Students - Nurani, Qoim (Magister Pendidikan Agama Islam Universitas Islam Nusantara, 2022)
This research examines learning the Hiwar method in improving Arabic speaking skills at the elementary school level. Innovations in this learning method are expected to improve the quality of the process and learning outcomes. The hiwar method emphasizes the activeness of students in the classroom through active student involvement in the learning process. Students are encouraged to learn through their own active involvement and teachers encourage students to have experiences in conducting experiments that allow them to find principles for themselves. The method used in this research is a qualitative descriptive method, namely research that describes what is present or occurs in a particular field or area. The data collected is classified or grouped according to its type, nature or condition. The results of this study indicate an increase in students' speaking skills with the Hiwar method. This can be proven from the enthusiasm of students and the value of student learning outcomes tends to increase.